Dimethylnitrosamine (DMN) pre-treated rats and protective effect of Vernonia amygdalina post-treatment on liver function - Usunobun, Usunomena; Anyanwu, Gabriel (International Journal of Pharmacology and Toxicology, 2016)
Background: Liver disease and toxicity is common, especially with many drug treatments. The effect of Vernonia amygdalina ethanolic leaf extract post-treatment on rats pre-treated with dimethylnitrosamine (DMN) was evaluated. Methods: Male wistar rats were orally administered DMN (single dose of 25 mg/kg) on first day and thereafter post-treated with 100 and 200mg/kg ethanolic leaf extract of Vernonia amygdalina for seven days. Analysis of serum concentrations of albumin, total protein, total bilirubin and glucose were carried out. Results: Administration of DMN alone to rats significantly increased glucose and total bilirubin concentration (P < 0.05) in the serum while it significantly reduced (P<0.05) serum total protein and albumin concentrations when compared with controls. However, post-treatment of DMN administered rats with 100 and 200 mg/kg ethanolic extract leaf of Vernonia amygdalina significantly (P<0.05) reversed these changes in a concentration dependent manner. Conclusion: In conclusion ethanolic leaf extract of Vernonia amygdalina have a potent hypoglycaemic and hepatoprotective action against dimethylnitrosamine-induced liver damage in rats may be due to its antioxidant properties.